Brand Knowledge and Organizational Loyalty as Antecedents of Employee-Based Brand Equity: Mediating Role of Organizational Culture - Liu, Xiaoming (Frontiers in Psychology, 2022)
This study tends to explore the impact of brand knowledge and organizational loyalty under the mediating role of organizational culture on employee-based brand equity (EBBE). For this purpose, employees of the hospitality sector were contacted to collect data through personally administrated questionnaires. Already established scales were used to devise instruments. Data were collected in two waves to minimize the common method bias. In the first wave, a total of 600 questionnaires were distributed, out of which 400 were received back, while in the second wave, remaining respondents were approached who have filled the survey in the first wave, and only 320 were received back, from which the partial and incomplete questionnaires were discarded, and at the end, 306 questionnaires were left. These final and completed responses were used for the data analysis and inferential purpose in this study. Collected data have been analyzed through Structural Equation Modeling by using Smart PLS 3 software. The assessment of measurement and structural model indicated a good model fit, and results indicate that EBBE is influenced by organizational loyalty and brand knowledge positively. Moreover, the mediating role of organizational culture has also been proved.